The Effect of Teams Games Tournament Assisted by Flipcharts on the Cognitive Abilities of Elementary School Students - Amelia, Devana Hananda; Rezania, Vanda; Fihayati, Zuyyina (Mimbar Sekolah Dasar, 2023)
The problem of the lack of teacher innovation in learning is the main factor in the occurrence of a boring classroom atmosphere, so students often experience difficulties in learning certain materials. The objective of this study is to determine the cognitive abilities of elementary school students by using media and a cooperative learning model of teams games tournament. This research was conducted at SDN Wunut II Porong. True-Experimental Design with Posttest-Only Control Group Design, using quantitative research type. The sample of this study was class VI consisting of 30 students using simple random sampling data collection using instruments in multiple-choice tests containing indicators of the cognitive domain. The results showed that when compared to the posttest value of the control class using the lecture method, the experimental class using the teams games tournament type cooperative learning model assisted by flipchart had a superior value on students' cognitive abilities. It is anticipated that using the teams games tournament learning paradigm to social studies content using flipcharts will enhance student learning outcomes and strengthen cognitive skills. The success is influenced by students who are actively involved in games and competitions so as to make students excited in the learning process.